PROSES PENGHAPUSAN BARANG MILIK DAERAH PADA BAGIAN ASET DI DPRD KABUPATEN BANDUNG - Galih Anggara Putra; Ramayani Yusuf (SECAD, 2025)
This study aims to analyze the process of disposal of Regional-Owned Assets (Barang Milik Daerah/BMD) at the Secretariat of the Bandung Regency Regional House of Representatives (DPRD). Proper asset disposal is essential to ensure efficient, transparent, and accountable asset management in accordance with prevailing regulations. This research employs a descriptive qualitative method, with data collected through direct observation, interviews with asset management officers, and documentation review. The disposal process includes stages of asset identification, condition assessment, administrative proposal, approval by authorized officials, and implementation through destruction, auction, transfer, or grants. The findings indicate that the disposal of BMD at the Secretariat of DPRD Bandung Regency has generally been conducted in accordance with applicable regulations and administrative procedures. However, several constraints were identified, particularly related to internal supervision and data accuracy. Therefore, strengthening internal control and conducting periodic audits are necessary to enhance accountability and improve the effectiveness of regional asset management.